(untitled) (Contemporary Mathematics, 2024)
In this research, the solution of linear partial differential equations (PDEs) is obtained using the Laplace transform. The solution of linear PDEs using the Laplace transform has the advantage that an arbitrary constant is specifically displayed as an initial value. Even if the Laplace transform used as a tool is replaced with many other Laplace-type transforms, the attempted method is valid. Incidentally, the solution to Example 2 is obtained using ChatGPT and compared with the exact solution.